Adjusted Versus Fixed Doses of the Low-Molecular-Weight Heparin Fragmin in the Treatment of Deep Vein Thrombosis - Alhenc-Gelas, M; Guernic, C Jestin-Le; Vitoux, J F; Kher, A; Aiach, M; Fiessinger, J N; Fragmin-Study Group (Thrombosis and Haemostasis, 1994)
Treatment monitoring based on a laboratory parameter increases the efficacy and safety of standard heparin therapy, but it is not known if this also applies to low-molecular-weight heparin (LMWH) therapy of acute deep vein thrombosis (DVT). In a prospective randomized trial involving 122 consecutive patients, group A (58 patients) received a weight adjusted dose of Fragmin (100 IU/kg) subcutaneously twice a day throughout the treatment period (10 days ± 1), while in group B (64 patients) the dosage was based on the results of an anti factor Xa (anti Xa) amidolytic assay to obtain a target concentration from 0.5 to 1 IU/ml. AntiXa and antithrombin activities were also measured retrospectively on frozen plasma from all patients. The two regimens were comparable in terms of hemorrhagic complications (4 in group A and 3 in group B). Bilateral ascending phlebography was performed before inclusion and at the end of LMWH treatment. Treatment efficacy, based on Marder’s score, did not differ between the two groups (p = 0.3). Dosage adjustment to between 0.5 to 1IU anti-Xa/ml does not therefore appear to improve the efficacy or safety of LMWH tieatment. However, correlations between the change in Marder’s score and both anti-Xa (p <0.001) and antithrombin activity (p <0.001) were observed, suggesting a relationship between the degree of FXa or thrombin inhibition and antithrombotic activity.